Implementasi Pendidikan Sains Berbasis Steam Untuk Membentuk Generasi Inovatif Di Sekolah Dasar - Nurlian Nurlian; Mildayanti Mildayanti; ST. Rohani; Titi Anita; Eko Prayudi (Jurnal Sultra Elementary School, 2024)
STEAM (Science, Technology, Engineering, Arts, and Mathematics)-based education has become a relevant learning approach in responding to the challenges of the 21st century. This study aims to analyze the implementation of STEAM-based science education in elementary schools in order to form an innovative generation. Literature studies were conducted by reviewing articles, journals, and books related to the application of STEAM in elementary education. The results show that the STEAM approach can improve creativity, critical thinking skills, collaboration, and problem solving in students. In addition, the integration of art in STEAM can create more holistic learning. Challenges in implementation include limited resources, teacher training, and appropriate curriculum development. Recommendations are provided to support the successful implementation of STEAM in elementary schools.